2022
DOI: 10.3389/fphar.2022.862763
|View full text |Cite
|
Sign up to set email alerts
|

Codonopsis pilosula Polysaccharide Improved Spleen Deficiency in Mice by Modulating Gut Microbiota and Energy Related Metabolisms

Abstract: Codonopsis Radix (CR) is an important traditional Chinese medicine used for the treatment of spleen deficiency syndrome (SDS). Codonopsis pilosula polysaccharides (CPP) in CR are considered to be responsible for tonifying the spleen function; however, the mechanisms of the polysaccharides have remained unclear. This study aimed to investigate the treatment mechanisms of CPP in SDS mice using a combinational strategy of 16S rRNA gene sequencing and targeted metabolomics. Here, studies demonstrated that CPP had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…(C. tangshen) [1,2]. Based on the results of several past studies, both polysaccharides, and oligosaccharides in Codonopsis Radix possess good pharmacological activities [3][4][5]. In addition, our recent experiments confirmed that the 95% ethanol-extracted fraction of Codonopsis Radix exhibited significant pharmacological activities, and Wang [6] isolated a series of triterpenoids and sterols from the 95% ethanol extract of Codonopsis Radix.…”
Section: Introductionmentioning
confidence: 82%
“…(C. tangshen) [1,2]. Based on the results of several past studies, both polysaccharides, and oligosaccharides in Codonopsis Radix possess good pharmacological activities [3][4][5]. In addition, our recent experiments confirmed that the 95% ethanol-extracted fraction of Codonopsis Radix exhibited significant pharmacological activities, and Wang [6] isolated a series of triterpenoids and sterols from the 95% ethanol extract of Codonopsis Radix.…”
Section: Introductionmentioning
confidence: 82%
“…Spleen deficiency is often accompanied by immune deficiency, which generally manifests as decrease in immune organ index, elevated levels of pro-inflammatory cytokines, and impaired intestinal barrier 5 , 11 , 30 . It has also been found in the present study that decreases in immune organ (spleen and thymus) index, increased levels of pro-inflammatory cytokines IL-6, and TNF-α and the significant inflammatory cell infiltration in colon in the Model group.…”
Section: Discussionmentioning
confidence: 99%
“…SDS has also been reported to be closely related to intestinal microbial disturbances, which refers to significant changes in the structure and composition of gut flora 1 , 10 , 11 , 28 , 36 . It has been reported that non-starch polysaccharides extracted from Codonopsis Radix , Radix Aconiti Lateralis Preparata and Sijunzi compound could regulate the structure and composition of intestinal flora and promote the reproduction of intestinal probiotics 3 , 5 , 37 . In present study, PHP not only have a positive effect on the diversity and abundance of probiotics, but also make the structure and composition of intestinal microorganisms close to those in the Ctrl group.…”
Section: Discussionmentioning
confidence: 99%
“…It has the effects of strengthening the spleen, moistening the lungs, activating the blood, and generating fluids ( Wang J. et al, 2024 ). It is often studied by researchers as a stand-alone agent in addition to being used in combination with other drugs ( Cao et al, 2022 ). We summarize the research progress of CP in diseases in the last 5 years.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…These active ingredients have a wide range of roles in the digestive system, metabolic system, nervous system, cardiovascular system and cancer treatment. For example, Codonopsis polysaccharides (CPPs), found in CP, is thought to play a role in increasing splenic tone ( Cao et al, 2022 ). However, the mechanism of action of CP in disease treatment, whether used alone or in combination with other drugs, is unclear.…”
Section: Introductionmentioning
confidence: 99%